PENGARUH LIKUIDITAS SAHAM TERHADAP STOCK PRICE CRASH RISK PADA PERUSAHAAN INDUSTRI CONSUMER GOODS DI BURSA EFEK INDONESIA PADA TAHUN 2010-2019 - Amizza Manik Mayang; Ossi Ferli (Jurnal Ilmu Manajemen, 2022)
This study aims to obtain empirical evidence of the effect of stock liquidity on the stock price crash risk. Stock liquidity is measured by measuring Trading Volume Activity (TVA). The stock price crash risk is calculated using the negative coefficient formula model of skewness (NCSKEW). The sampling method was purposive sampling. The sample includes 8 consumer goods companies on the Indonesia Stock Exchange (BEI) from 2010 to 2019. The hypothesis in this study was tested using multiple linear regression analysis models with Eviews9 software. The result shows that stock liquidity has a significant negative effect on stock price crash risk. Size as a control variable also has no significant effect on stock price crash risk. However, the second control variable, price on book value (PBV), has a significant positive effect on stock price crash risk. The results indicate that a critical factor in reducing stock price crash risk is high investor interest to monitor the company's development.